Населення лiсостепової зони України в скiфську добу - Рудич, Т.О. (Археологія, 2020)
Розглядається питання антропологічного співвідношення
груп скіфської доби лісостепової та степової зон України, а також місце лісостепових груп у колі хронологічно
близьких серій Європи. Тема состава населения Лесостепи Украины скифского времени рассматривалась историками, археологами,
лингвистами и антропологами. В последнее время база данных по антропологии населения степной Скифии расширилась. Это позволяет по-новому посмотреть как на население степной, так и лесостепной зоны Украины
этого периода.
В данной работе краниологические материалы лесостепных и степных серий рассматривались в кругу групп,
представляющих население Прибалтики, Центральной и Южной Европы. Статистическая обработка материала
производилась с использованием пакета программ Systat.
По результатам анализа антропологический состав населения лесостепной зоны Украины скифского времени
не был однородным.Однако четко выделяется доминирующийморфологический компонент. Это долихокранный
морфотип с длинной, узкой черепной коробкой, средними размерами лица, которое резко профилированное в
горизонтальной плоскости. Морфотип определяет средние характеристики большинства суммарных серий мужских черепов.
Население лесостепной и степной зоны Украины составляют два разных антропологическихмассива, границы
которых не пересекаются. Лесостепное население нельзя рассматривать в качестве локального варианта скифского антропологического массива.
Население лесостепной и степной зоны Украины было сформировано на разной морфологической основе.
Основной массив населения Лесостепи Украины четко демонстрируют северо-западное направление антропологических связей. Его антропологический тип сформировался на основе популяций, которые имеют генетические
истоки в культурах шнурового круга. Шнуровой массив населения был не однородным. Мы говорим о той части
популяций шнуровой керамики, на основе которой сформировался морфологический тип, который в исторической перспективе стал доминирующим у балтов в эпоху железа.
Большая часть серий лесостепной зоны скифского времени морфологически и статистически близки популяциям Восточной Прибалтики эпохи железа. Однако фиксируется и население, которое происходит из групп,
связанных с ираноязычным миром.
Нами для анализа использовались лишь материалы из погребений по обряду ингумации. Кремация не оставляет материалов для работы исследователей, которые занимаются этнической антропологией. Следовательно,
часть информации о населении региона закрыта. Теоретически население лесостепной зоны Украины скифского
времени могло быть полиморфным. The issue on the composition of the forest-steppe population of Ukraine of the Scythian time was considered by historians,
archaeologists, linguists and anthropologists. Recently, the database on the anthropology of the steppe Scythia population
has been expanded. It allowed researchers to take a fresh look at both the population of the steppe and forest-steppe zones
of Ukraine of the mentioned period.
In the article, craniological materials of the forest-steppe and steppe series were considered in a circle of groups
representing the population of the Baltic region, Central and Southern Europe. Statistical processing of material was
performed using the Systat software package. According to the analysis, the anthropological composition of the Ukrainian forest-steppe zone population of the
Scythian time was not homogeneous. However, the dominant morphological component is clearly distinguished. This is a
dolichocran morphological type with a long, narrow skull, average face sizes, which is sharply profiled in a horizontal plane.
Certain morphological type determines average characteristics of most of the summarized series of male skulls.
The population of the forest-steppe and steppe zones of Ukraine is presented by two different anthropological massifs
whose boundaries do not intersect. The forest-steppe population cannot be considered as a local version of the Scythian
anthropological massif.
The population of the above mentioned area was formed on a different morphological basis. The main massif of the
population of the Ukrainian forest-steppe clearly demonstrates the north-western direction of anthropological ties. Its
anthropological type was formed on the basis of populations that have genetic origins in the Corded Ware circle cultures.
The Corded Ware culture population was not homogeneous. Namely, that part of the Corded people, on the basis of which
a morphological type was formed, which in a historical perspective became dominant among the Balts in the Iron Age.
Most of the series of the forest-steppe zone of the Scythian time are morphologically and statistically close to the
populations of the Eastern Baltic Iron Age. However, the population that comes from groups that are associated with the
Iranian-speaking world is also fixed.
For analysis, there were used only materials from burials according to the ritual of inhumation. Cremation does not
leave materials for the work of researchers who are engaged in ethnic anthropology. Consequently, some of the information
on the region population is closed. Theoretically, the population of the forest-steppe zone of Ukraine of the Scythian time
could be more polymorphic.